Impact of Modern Lifestyle on the Health of Medical Students at Libyan International Medical University - Elsaid, Amina; Nadia Eldarogi,; Mawada Al Subaihi,; Yahya Al Subaihi, (AlQalam Journal of Medical and Applied Sciences, 2025)
A healthy lifestyle is a way of living that reduces the chances of experiencing illness. Lifestyle is an essential factor in health. Unhealthy behaviour can lead to illness, disability, and even death. This study was conducted to determine the impact of modern lifestyle on medical student health in the Libyan International Medical University. A cross-sectional study was carried out among undergraduate medical students in Libyan International Medical University, Benghazi, Libya, for three months (May, June and July in 2023), including students of all ages, both sexes, and all academic years. A total of 1500 students were enrolled in the university. About 71.3% of students had insomnia, 49% had an eating disorder, and 21% had a panic attack. A significant difference between genders, 70% of students who had insomnia and sleeping disorders, panic attacks were female, and between academic years, the fourth year had a higher percentage of insomnia. There was a statistical association with insomnia among the students who didn’t eat fruits and vegetables. While students who do not exercise have panic attacks during their academic years. Students who had skipped breakfast had more distractions and a lack of focus during academic years. Some modern life behaviors like skipping breakfast, not eating fruits and vegetables, eating fast food, not doing exercise, and not sleeping well harm the health of medical students. نمط الحياة الصحي هو أسلوب حياة يقلل من فرص الإصابة بالمرض. نمط الحياة عامل أساسي في الصحة. يمكن أن يؤدي السلوك غير الصحي إلى المرض والإعاقة وحتى الموت. أجريت هذه الدراسة لتحديد تأثير نمط الحياة الحديث على صحة طلاب الطب في الجامعة الطبية الدولية الليبية. أجريت دراسة مقطعية بين طلاب الطب الجامعي في الجامعة الطبية الدولية الليبية، بنغازي، ليبيا، لمدة ثلاثة أشهر (مايو ويونيو ويوليو في عام 2023) بما في ذلك الطلاب من جميع الأعمار والجنسين وجميع السنوات الدراسية. تم تسجيل ما مجموعه 1500 طالب في الجامعة. كان حوالي 71.3٪ من الطلاب يعانون من الأرق، و 49٪ يعانون من اضطراب في الأكل، و 21٪ يعانون من نوبة هلع. كان هناك فرق كبير بين الجنسين، 70٪ من الطلاب الذين يعانون من الأرق واضطرابات النوم ونوبات الهلع كانوا من الإناث، وبين السنوات الدراسية، كان لدى السنة الرابعة نسبة أعلى من الأرق. كان هناك ارتباط إحصائي بالأرق بين الطلاب الذين لم يتناولوا الفاكهة والخضروات. بينما يُصاب الطلاب الذين لا يمارسون الرياضة بنوبات هلع خلال سنواتهم الدراسية، فإن الطلاب الذين تخطوا وجبة الإفطار كانوا أكثر عرضة للتشتت وقلة التركيز خلال سنواتهم الدراسية. بعض سلوكيات الحياة العصرية، مثل تخطّي وجبة الإفطار، وعدم تناول الفاكهة والخضراوات، وتناول الوجبات السريعة، وعدم ممارسة الرياضة، وقلة النوم، تُضرّ بصحة طلاب الطب